2016
DOI: 10.1155/2016/4375418
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Is Overactivated in Left and Right Ventricles from Ischemic Hearts: An Intriguing Therapeutic Target

Abstract: Growing evidence indicates that reactive oxygen species (ROS) may play a key role in human heart failure (HF). Monoamine oxidase (MAO) is emerging as a major ROS source in several cardiomyopathies. However, little is known about MAO activity in human failing heart and its relationship with redox imbalance. Therefore, we measured MAO activity in the left (LV) and in the right (RV) ventricle of human nonfailing (NF) and in end-stage ischemic (IHD) and nonischemic failing hearts. We found that both MAO isoforms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
(71 reference statements)
2
35
0
Order By: Relevance
“…Here, we demonstrate that chronic sublethal doses of H 2 O 2 produced by MAO‐A in response to its endogenous (NE) or exogenous (Tyr) substrates can recapitulate all the features of senescence. This could have particular relevance in cardiac ageing, where MAO‐A is likely to be chronically activated due to: (a) sympathetic activation and enhanced release of norepinephrine from adrenergic nerves (Santulli & Iaccarino, 2016); and (b) overexpression of MAO‐A in the ageing heart (as shown in Figure 1a,b) or in age‐associated cardiac diseases (Manni et al, 2016; Villeneuve et al, 2013). In addition, the role of MAO‐A in senescence could be extended to different cell types, since MAO‐A has been characterized in many proliferative cells, such as fibroblasts and bone marrow mesenchymal stem cells, where its expression was significantly increased during ageing (Edelstein & Breakefield, 1986; Trouche et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that chronic sublethal doses of H 2 O 2 produced by MAO‐A in response to its endogenous (NE) or exogenous (Tyr) substrates can recapitulate all the features of senescence. This could have particular relevance in cardiac ageing, where MAO‐A is likely to be chronically activated due to: (a) sympathetic activation and enhanced release of norepinephrine from adrenergic nerves (Santulli & Iaccarino, 2016); and (b) overexpression of MAO‐A in the ageing heart (as shown in Figure 1a,b) or in age‐associated cardiac diseases (Manni et al, 2016; Villeneuve et al, 2013). In addition, the role of MAO‐A in senescence could be extended to different cell types, since MAO‐A has been characterized in many proliferative cells, such as fibroblasts and bone marrow mesenchymal stem cells, where its expression was significantly increased during ageing (Edelstein & Breakefield, 1986; Trouche et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…MAO-A is an isoform of FAD-dependent enzymes, that catalyzes oxidative deamination of catecholamines and serotonin in the heart, producing the corresponding aldehyde, H 2 O 2 , and ammonia. Previous studies have reported that MAO-A expression and activity increased in chronic cardiac diseases [108][109][110][111]. They found that OleA conferred cardioprotection, not simply by its antioxidant action, but through restoration of defective autophagic flux autophagy, reflected by auto-phagolysosome formation, measured by p62 and cathepsin-B levels increase, and the transcriptional factor EB (TFEB) activation and translocation to the nucleus.…”
Section: Oleuropein and Cardioprotectionmentioning
confidence: 99%
“…diovascular disease and Parkinsonʼs disease. MAO-A inhibitors have thus been advocated as potential treatment of congestive heart failure while MAO-B inhibitors may act as potential neuroprotective agents in neurodegenerative disorders [2,[11][12][13]. Interestingly, MAO-A activity has been found to be increased in certain types of cancer, and MAO-A inhibitors have thus been investigated as potential treatment of prostate cancer [14].…”
Section: Monoamine Oxidase Inhibition By Kavalactones From Kava (Pipementioning
confidence: 99%